Association of significant financial burden with survival for head and neck cancer patients treated with radiation therapy. (April 2021) - Ma, Sung Jun; Iovoli, Austin J.; Attwood, Kristopher; Wooten, Kimberly E.; Arshad, Hassan; Gupta, Vishal; McSpadden, Ryan P.; Kuriakose, Moni A.; Markiewicz, Michael R.; Chan, Jon M.; Hicks, Wesley L.; Platek, Mary E.; et al.
Highlights: HNC patients frequently struggle with financial difficulties. Financial toxicity was associated with worse OS and CSS in HNC. Methods to mitigate financial toxicity in HNC are needed. Abstract: Objective: To assess the association between financial toxicity and survival in patients with head and neck cancer (HNC). Materials and methods: Using a single-institution database, we retrospectively reviewed HNC patients treated at Roswell Park Comprehensive Cancer Center treated with definitive or postoperative radiation therapy between 2013 and 2017. Kaplan-Meier method and log-rank tests were used to analyze survival outcomes. Propensity score matching on all clinically relevant baseline characteristics was performed to address selection bias. All statistical tests were two-sided and those less than 0.05 were considered statistically significant. Results: Of a total of 284 HNC patients (age: median 61 years, IQR 55–67; 220 [77.5%] men), 204 patients (71.8%) received definitive radiation and 80 patients (28.2%) received adjuvant radiation. There were 41 patients (14.4%) who reported high baseline financial toxicity. Chemotherapy was used in 237 patients (83.5%). On multivariable analysis, those with high financial toxicity exhibited worse overall survival (hazards ratio [HR] 1.75, 95% confidence interval [CI] 1.05–2.94, p = 0.03) and cancer specific survival (HR 2.28, 95% CI 1.31–3.96, p = 0.003). On matched pair analysis of 66 patients, high financial toxicity remained associated with worse OS (HR 2.72, 95% CI 1.04–7.09, p = 0.04) and CSS (HR 3.75, 95% CI 1.22–11.5, p = 0.02). Conclusion: HNC patient reported baseline financial toxicity was significantly correlated with both decreased overall and cancer specific survival. These significant correlations held after match pairing. Further research is warranted to investigate the impact of financial toxicity in HNC and mitigate its risk.